Impacts of clustering of vegetable farmers in the Philippines - Rola-Rubzen, Maria Fay; Murray-Prior, Roy; Batt, Peter; Concepcion, S.; Real, R.; Lamban, R.; Axalan, J.; Montiflor, M.; Israel, F.; Apara, D.; Bacus, R. (Australian Centre for International Agricultural Research, 2013)
This assessment was made as part of a systematic process of evaluating the impacts of clustering vegetable farmers in the southern Philippines. Program theory was used to map the impacts. The performance of cluster and non-cluster farmers was compared. Farmers’ performance before and after clustering was also examined. The study found that, on average, cluster farmers had higher incomes than non-cluster farmers. Moreover, farmers increased their income by about 47% after clustering. Examining the returns on investment in the research project, it was found that the net present value (NPV) was 35.3 million pesos, the internal rate of return (IRR) 48.6% and the benefit:cost ratio (BCR) 2.47. When spillover effects were considered at a 5% adoption rate, the NPV, IRR and BCR increased to 106.9 million pesos, 81.5% and 3.8, respectively.